Care protocol for acute traumatic tissue injuries in prehospital mobile service - Bettega,Rodrigo Pereira (2021)
SUMMARY OBJECTIVE: The aim of this study is to elaborate a protocol for the care of acute traumatic tissue injuries in the prehospital mobile service. METHODS: An extensive search of anteriority that did not reveal the existence of such protocol in other services across the globe was carried out. Subsequently, the literature review was executed on Medline and Lilacs. Related and referenced scientific literature served as the basis for the elaboration and creation of the protocol and its flowchart. The complete protocol was then measured for expert judges with the Delphi methodology. A questionnaire (using the Likert scale) and the initial version protocol were sent by electronic means to 13 medical and nurse coordinators of all SAMU from Paraná. RESULTS: Seven experts returned completed questionnaires in the first round and five in the second round. Average required global content validation index was obtained for the validation requirements of the protocol and its flowchart. CONCLUSIONS: A protocol for the care of acute traumatic tissue injuries in the prehospital mobile service was developed and authenticated with the viability of routine professional use by the health professional.